NILAI – NILAI SPIRITUAL DALAM NOVEL GURU AINI KARYA ANDREA HIRATA DALAM PENGUATAN PENDIDIKAN KARAKTER DI ERA DIGITAL 4.0 - Siti Masrukhah; Wildan Habibi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2026)
In the digital era 4.0, where advances in technology and information have brought several impacts, both positive and negative impacts on the development of students' characters. Challenges such as decreased morality, increased dependence on the use of technology, and also the weakening of spiritual values make the world of education must find real solutions to these problems. One approach that can be done is through strengthening character education based on spiritual values. This study aims to 1) find out the spiritual values contained in the novel Guru Aini by Andrea Hirata and 2) find out the relevance of these spiritual values to strengthening character education in the digital 4.0 era. This research is a literature research with a qualitative approach. Primary data sources come from the novel Guru Aini, while secondary data come from books, journals, and other relevant literature. Data collection techniques use literature studies, and data analysis techniques use content analysis techniques and descriptive analysis. The results showed that in Guru Aini's novel, there are various spiritual values such as honesty, courage, simplicity, caring, responsibility, integrity, trust, gratitude, perseverance, and patience. The spiritual values in the novel have strong relevance to strengthening character education in this digital era, especially in the aspects of: leadership, personal responsibility, ethics, people skills, adaptability, self-direction, accountability, social responsibility, and personal productivity. Keyword : Spiritual Values, Character Education, Guru Aini